A case study on the residential space utilization of the kitchen and dining areas of students in a condominium building in Quezon City - Ventigan, Nichelle J. (College of Home Economics, University of the Philippines Diliman, 2019)
The study attempted to analyze the utilization of the kitchen and dining areas of selected residential condominium units. Specifically, it aimed to determine whether the design of the kitchen and dining areas affect the daily food preparation and consumption practices of the condominium owners. Seven college students were chosen as respondents, and five residential condominium units were analyzed. A qualitative research design was applied for the data collection by administering surveys, semi-structured interviews, observations, and photo documentation. Using user-centered design theory and Jacqueline Vischer's Habitability Pyramid, the study posited that the kitchen and dining areas provided in the condominium units affect the behavior of the respondents within the two spaces. Key findings of the study show that the kitchen has an effect on food-related practices and choices made by some of the students. Problems such as insufficient work and storage spaces and ventilation provided a poor food environment and thus, affected their decisions. Some were found to have limited their food choices to simpler and easy to prepare meals, while others opted to eat in fast-food restaurants or buy food from convenience stores. Furthermore, multi-functionality of the dining area was observed in some units. It was found that the functional necessity of the space for eating and studying preceded the desire to converse with fellow roommates. Consequently, this led to the loss of social interaction within the dining area. Further studies on the topic may include multiple condominium units in varying condominium buildings. It may also focus on families and professional living in residential condominium units, as they may present a different set of lifestyle, needs and requirements from the spaces.